2010
DOI: 10.1016/j.rbmo.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Redefining advanced maternal age as an indication for preimplantation genetic screening

Abstract: In this retrospective study, the utility of preimplantation genetic screening (PGS) in patients with advanced maternal age is evaluated. The patient population consisted of women aged 38-44years and included in a regular IVF programme with or without PGS analysis. Transfer rate, ongoing implantation rate and ongoing pregnancy rate were the main outcome parameters measured. A trend of better ongoing pregnancy rate per oocyte retrieval was observed in patients aged 38 and 39years in the non-PGS group when compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 60 publications
0
25
0
6
Order By: Relevance
“…PGS was encouraged in women over 40 years old [25], though the latest meta-analysis discourage the using of PGS [26], patients selection is an important procedure in PGS. Comparative genomic hybridization (CGH) and array-CGH were widely used now for PGS which could make the result more sensitive and exact [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…PGS was encouraged in women over 40 years old [25], though the latest meta-analysis discourage the using of PGS [26], patients selection is an important procedure in PGS. Comparative genomic hybridization (CGH) and array-CGH were widely used now for PGS which could make the result more sensitive and exact [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…PGS was indicated for AMA, in patients over 38 years old until May 2010. After that, the AMA group was re-defined as patients over 40 years old due to a retrospective analysis of the results from our lab [13]. Also mixed indications were found in 47 of those 320 couples, in which AMA was the secondary indication for 22 RM couples, 14 RIF couples and 7 couples with a previous chromosomally abnormal gestation.…”
Section: Clinical Application Of Arraycghmentioning
confidence: 99%
“…Low responders, for instance, can benefit from accumulation of oocytes through vitrification as it allows them to achieve similar clinical outcomes as normo-responders [13]. Moreover, this strategy is also attractive for patients of advanced maternal age (a more difficult group to treat) who, in addition to being low responders, require preimplantation genetic screening [14]. On the contrary, vitrification of oocytes (and embryos) has also proven to work with patients at risk of developing OHSS and represents a solution when embryo transfer needs to be delayed [15,16].…”
Section: Freeze-all-why?mentioning
confidence: 99%
“…A recent study by our group [79] revealed no difference in terms of ongoing pregnancy and live birth rates between normo-responder patients who underwent fresh and deferred embryo transfers. This was a retrospective study that included 882 patients aged 20-44 who underwent their first or second IVF/ICSI cycle, in which a normal oocyte yield [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] was obtained. Patients were divided into two groups: 364 (41.3 %) underwent fresh embryo transfer and 518 (58.7 %) were submitted to freeze-all, according to their doctor's preference.…”
Section: Freeze-all For Whom?mentioning
confidence: 99%